Beyond the market : the social foundations of economic efficiency - Beckert, Jens, 1967- (Princeton University Press, 2002)
Beyond the Market launches a sociological investigation into economic efficiency. Prevailing economic theory, which explains efficiency using formalized rational choice models, often simplifies human behavior to the point of distortion. Jens Beckert finds such theory to be particularly weak in explaining such crucial forms of economic behavior as cooperation, innovation, and action under conditions of uncertainty--phenomena he identifies as the proper starting point for a sociology of economic action. Beckert levels an enlightened critique at neoclassical economics, arguing that understanding e.